Exploring stress management training provision for students in the context of post-secondary education: evidence from Greece. Issue 2 (6th May 2014) - Panagiotakopoulos, Antonios
Abstract : Purpose: – The aim of this paper is to investigate the extent to which post-secondary educational institutions in Greece have incorporated into their curriculum modules related to occupational stress management in order to equip graduates with the required knowledge to cope with the stress caused by the precarious and intensified nature of contemporary jobs. Design/methodology/approach: – In the present study, extensive secondary data analysis was undertaken, which was complemented by an empirical quantitative survey. Regarding the secondary data analysis, an in-depth examination of all the available core and elective modules was undertaken in 150 programs of 35 Greek post-secondary educational institutions. The analysis involved the detailed examination of the curriculum content across 20 disciplines. As for the empirical part of the study, a self-administered questionnaire survey was used involving 100 students across the 20 selected disciplines. Findings: – The findings revealed that in Greek post-secondary education there is minimal systematic training provision for students around work-related stress management. The results show that stress management education is not incorporated in the curriculum as part of a key skills development scheme (either in the form of stand-alone modules or embedded in the curriculum) in most disciplines, which raises questions on the contribution of educational institutions in developing graduate employability. Research limitations/implications: – The study argues that there is an immediate need for post-secondary educational institutions across the country to develop relevant modules around managing occupational stress in order to respond to society's contemporary needs. To this end, the study argues that stress management training should be introduced in all VET and HEIs in Greece in the form of compulsory, stand-alone modules across all disciplines. The module should cover at least three main thematic areas: symptoms of work-related stress; impact of stress on individuals and organizations; and ways to cope with occupational stress. Practical implications: – The present study is particularly relevant to education policy makers throughout the world, due to the high levels of organizational change and uncertainty generated by the present global financial crisis and recession. Stress at work is likely to remain a "hot" topic in the agenda of government officials across the world, and finding ways to cope with occupational stress is likely to become a key challenge of post-secondary education. Originality/value: – Despite the importance of stress management training for graduate employability, very few studies have been conducted around that topic. This work comes to fill a significant knowledge gap in relation to the nature and extent of occupational stress management training provision for students in the context of post-secondary education.